Variabilidade genética dos hemotipos no cavalo puro sangue de corrida do Rio Grande do Sul, Brasil - Pozzobon, Silvia Fátima (2001)
Blood samples taken from 2.679 thoroughbred horses born in 1998 and 1999 in Rio Grande do Sul were blood typed. Typing was performed at 15 loci, 7 blood groups (A, C, D, K, P, Q, and U) were determined by agglutination and hemolysis tests and 8 protein systems (albumin (Alb), transferrin, (Tf), A1 glycoprotein (Xk), esterase (Es), vitamin D binding protein (Gc), proteinase inhibitor (Pi), hemoglobin (Hb) and 6 phosphogluconate dehydrogenase (6-PGD)) by horizontal electrophoresis on polyacrylamide and starch gels and isoelectric focusing gel electrophoresis. From the phenotypes and genotypes obtained allelic frequency was calculated in the 15 systems. The most frequent allele in each system was: Aadf, Ca, Ddkl, Ka, P -, Qabc, U-, Alb B, Xk K, Gc F, Es I, Tf F1, Pi L, Hb BII, 6-PGD F. The total number of alleles found was 59. Average heterozygosity and probability of exclusion at the 15 loci was 0,3670  0,0635 and 87%, respectively. The inbreeding level (Fis) determined only by the protein systems, was only significant for Hb (Fis=-0,002, p<0,05). Nei`s distance was used to compare genetic variability between the studied population and thoroughbred populations typed in the USA and Chile. Genetic distance between these populations was very close. Genetic variability observed in thoroughbreds from Rio Grande do Sul, Brazil, was almost identical to thoroughbred populations from other countries.